Electoral systems, ethnic diversity and party systems in developing democracies. (June 2017) - Lublin, David
Abstract: Party system nationalization is often viewed as critical to national unity, the production of public goods, and may have implications for democratic success. This paper assesses the impact of ethnic diversity and electoral rules in 74 economically developing democracies. Contrary to past studies, majoritarian electoral systems heighten the tendency of ethnic diversity to reduce nationalization while proportional representation greatly reduces its impact. Presidential systems produce higher levels of nationalization than parliamentary systems but the effect reverses as the number of presidential candidates increases. Though ethnic party bans may increase nationalization, ballot access requirements, the level of freedom, and relative prosperity have no effect.